1994
DOI: 10.1080/1066892940180502
|View full text |Cite
|
Sign up to set email alerts
|

Orientation Program Considerations for New Community College Faculty

Abstract: The roles and expectations of community college faculty members have grown more complex as their institutions change to meet the needs of their respective communities. Whereas faculty development programs have assisted in the creation of programs and strategies to help faculty cope with change, the initial orientation of faculty to their college proves to be vital to their performance, success, and length of tenure. This study was designed to supply an understanding of community college faculty perceptions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…A lack of effort to welcome an individual into a workplace has the potential to alienate and marginalize the employee. More practically, the literature on faculty orientation programs reveals that such programs can help new academic staff better integrate into their institution (Miller & Nadler, 1994;Morin & Ashton, 2004). A formalized onboarding program could, arguably, reduce the wider opinion of adjuncts.…”
Section: Resultsmentioning
confidence: 99%
“…A lack of effort to welcome an individual into a workplace has the potential to alienate and marginalize the employee. More practically, the literature on faculty orientation programs reveals that such programs can help new academic staff better integrate into their institution (Miller & Nadler, 1994;Morin & Ashton, 2004). A formalized onboarding program could, arguably, reduce the wider opinion of adjuncts.…”
Section: Resultsmentioning
confidence: 99%
“…These perceptions did not differ based on either institutional size or mission Miller & Nadler, 1995). A similar research project revealed that the standards, with minor revisions, were also appropriate for use in faculty orientation programs (Miller & Nadler, 1994).…”
Section: Background and Research Methodsmentioning
confidence: 99%
“…Accepting the notion of faculty quality as an indicator of institutional quality, there is a paramount need to for the institution to invest in faculty at all stages of their careers. As argued by Nadler and Miller (1994), continued faculty growth and performance need to be early components of a faculty member's academic career, and actually begin when the faculty member steps foot on campus. Largely, this is a transitional phase in the development of a faculty member, and subsequently, institutions have a responsibility to create an atmosphere, environment, and culture that helps faculty members succeed.The concern for the College of Education at San Jose State University has been somewhat more complex than facing the need for long-term faculty growth.…”
mentioning
confidence: 99%